Perancangan Aplikasi Sistem Pendukung Keputusan Penentuan Tahfizh Terbaik Menggunakan Metode Simple Additive Weighting (SAW) Studi Kasus: STP Khoiru Ummah Serpong - Ibnu Hajar (OKTAL : Jurnal Ilmu Komputer dan Sains, 2025)
Tahfizh, the memorization of the Qur’an, requires persistence, accurate recitation, and comprehension. In institutions such as STP Khoiru Ummah, assessing students to determine the best tahfizh is often challenging because the manual process is time-consuming and prone to bias. To address this, a Decision Support System (DSS) was developed to support the selection process. The system applies the Simple Additive Weighting (SAW) method, which is suitable for multi-criteria decision-making. Criteria such as memorization quality, tajwid accuracy, fluency, and behavior are considered in the assessment. The development adopts the Rapid Application Development (RAD) model to ensure efficiency and adaptability based on user requirements. This research is expected to produce a system that enhances accuracy, transparency, and efficiency in selecting the best tahfizh, thereby contributing to the improvement of Qur’an memorization education at STP Khoiru Ummah Serpong.